Potential of Potato Peel as Substrate for Amylase Production in Solid State Fermentation - Pachhade, D.; Veer, P. (Journal of Scientific Research, 2025)
Microbial amylases have extensive commercial applications in various sectors such as food, beverages and pharmaceutical industries. In the present study, amylase producing bacterial strain was isolated from soil sample collected from garden campus of S. M. Joshi College, Hadapsar, Pune, Maharashtra. Primary screening of amylase producers was done on agar plates containing starch as substrate. Among 6 isolates, the potential strain was identified as Bacillus subtilis based on morphological cultural and biochemical tests. The solid-state fermentation was carried out using 20 % potato peel as substrate. The optimized physicochemical parameters were identified as pH 7, room temperature (~30 °C), 48 h and 7.5 % substrate concentration. The amylase activity was further improved in presence of 0.2 % (w/w) peptone, 0.02 % MgSO4·7H2O, 0.04 % CaCl2·2H2O and 0.04 % KH2PO4. Additionally, the optimized physicochemical and nutritional parameters reduced the fermentation time period by 50 % and gave optimum yield of enzyme in 24 h. Thus, the present study highlights the potential of B. subtilis strain to produce significant yield of amylase using agricultural wastes like potato peels.